Nilai-Nilai Pendidikan Islam Pranatal Dalam Buku Profil Orang Betawi Karya Ridwan Saidi - Dicky Setiady (Journal on Education, 2023)
This research aims to find out the process of internalizing prenatal Islamic education values in Betawi tradition, analyze the values contained therein, and identify the factors that hinder and support it. The research was conducted using a qualitative method of document analysis from the book "Profil Orang Betawi" by Ridwan Saidi with descriptive analytic presentation. The results of this research indicate that the process of internalizing prenatal Islamic education values in Betawi tradition includes the traditions of nyerep-nyerepin, duduk nikah, and nuju bulanin. The values contained in these traditions are religious values in the form of faith and moral values, as well as social values in the form of mutual cooperation. The supporting factors are the roles of schools, families, and communities in instilling Islamic education values, while the inhibiting factors are negative globalization trends and the loss of Betawi cultural knowledge due to the passing of Betawi figures. Therefore, cooperation among the community, family, and school is needed to strengthen Betawi culture based on Islamic education.